On the alleged need to strictly "Europeanize" the German Energiewende - Sebastian Strunz; Erik Gawel; Paul Lehmann (Helmholtz-Zentrum für Umweltforschung (UFZ), 2014)
Germany has embarked on an ambitious project to transform its energy system until 2050 - the so-called Energiewende. Some critics contend that the Energiewende imposes unneces-sary and avoidable welfare losses due to a lack of integration within the EU. In contrast, these critiques largely miss the point because the asserted lack of integration cannot be pinned on the Energiewende and the welfare consequences of EU-wide integration are less clear than the critiques imply.
Keywords: 330